Towards "digital sovereignty": Explaining digital repression in Russia - Aram Terzyan (CES Working Papers, 2023)
This paper explores the main features of digital repression in Russia, especially in the context of the Russian invasion of Ukraine. The repression of digital activism is not a new phenomenon in Russia; however, it gained fresh momentum during the Russian-Ukrainian war. Security has been used as a pretext to expand the state's authority at the cost of individuals' rights and freedoms. To control political narratives, suppress online dissent and surveil regime critics, the government has significantly tightened the national legislation through its media regulator, Roskomnadzor. The aftermath of the war, harsh sanctions and increased anti-regime movements have also deepened Russia's aspirations toward 'digital sovereignty'. Meanwhile, regardless of a number of important initiatives in this direction, domestic digital space still remains an ambitious goal to be fulfilled. This paper concludes that, along with other devastating consequences, the war in Ukraine will provoke further digital repression in Russia aimed at achieving the Kremlin's goal of "digital sovereignty".
Keywords: 330; Russia; digital repression; human rights; online space; 'digital sovereignty'